Seasonal changes in strength and power in elite rugby league: A systematic review and meta-analysis - Redman, K. J.; Kelly, V. G.; Beckman, E. M. (Journal of Sports Science & Medicine, 2021)
The ability of a rugby league player to express high levels of strength and power is crucial for success in competition. Although researchers have shown relationships between physical attributes and performance, there is a lack of information related to changes in strength and power across various phases of the season. The purpose of this review was to identify the magnitude of change in muscular strength and power during different phases of an elite rugby league season. Percentage change and effect size were calculated to evaluate the magnitude of changes in strength and power. Meta-analyses were conducted to provide pooled estimates and 95% confidence intervals. Twelve studies were included; six reported changes following pre-season training, two during the competition phase and four examined changes over multiple seasons. Pooled estimates indicated large increases in upper and lower body strength 0.81 [0.43-1.19] and 1.35 [0.79-1.91], respectively, following pre-season training. Studies incorporating predominantly heavier loads (p 80% 1 RM) in training reported greater increases in maximal strength than studies completing lighter loads. Four studies used a wave-like programming strategy to obtain large improvements in strength and power 0.91 [0.36-1.45] and 0.90 [0.22-1.57], over multiple seasons. The results of this review highlight the limited current evidence and provides a preliminary reference point for strength and conditioning coaches aiming to develop and maintain strength and power across various stages, and over multiple seasons. Importantly, the results also indicate that higher loads result in greater increases in strength than lower loads.